Effects of (Red Bull) energy drink in developing some physical capacities and heart rate in Koya University handball team (Raparin Journal of Humanities (RJH), 2023)
This study aimed to the followings:• Identifying the level of some of the functional and physical talents possessed by the players that were selected from Koya University.• An introduction to the effects that alcohol (red bull) has on some of the functional and physical capacities of a selected group of Koya University athletesThe research hypothesis was:• There are significant differences between the pre and post- test results in some physical aspects and heart rate.Performance trial-design via experimental approach was used for its suitability with the research problem. Handball players were chosen from Koya University consisting of six players. The practical experiment was drinking the energy drink (Red Bull، 250ml) for five days and in the sixth day drink one can of red bull about one hour before the post tests. Following a discussion of the findings and the application of some straightforward statistical tools، the following findings emerged from the research:• There is no effect of energy drink (red bull) on improving the level of physical capacities.• No significant differences between the outcomes of the minute test carried out by indigenous people and those carried out by outsiders.• There is a significant difference in the heart rate between the pre and post- tests.Recommendations:• According to the research، energy drink is not recommended to the public before performing effort. This is due to the fact that this energy drink is not sufficient to boost the physical capacities in the participants of the study.• Raising the athletes’ health awareness that energy drinks cannot be used as a substitute to natural energy and it is more detrimental to the body than it is useful.• Large amount shouldn’t be drank because it can have a detrimental effect on health and raises risk of having a heart disease، high blood pressure، kidney disease، and a number of other issues.• Undertaking further research and studies comparable to those described above with regard to various types of energy drinks، physical factors، and additional activities for a variety of sports.